Maṭlab al-Ṭālibīn: A Milestone in the Development of Tafsīr Literature in Kashmir - Naqash, Ghazi Nazir (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
This study examines Maṭlab al-Ṭālibīn fī Tafsīr Kalām Rab al-‘Ālamīn, a 16th-century tafsīr work by Ya‘qūb Ṣarfī, which is a significant milestone in the development of tafsīr literature in Kashmir. Despite its substantial influence on Kashmir’s intellectual history, Ṣarfī’s tafsīr has often been overlooked in academic research due to the poor quality of the manuscript and the limited availability of sources. This article adopts a qualitative approach to explore the unique structure of Ṣarfī’s tafsīr, which combines various disciplines such as tafsīr, ḥadīth, fiqh, kalām, and taṣawwuf, and examines how this work connects to the broader tradition of tafsīr in the Islamic world. Through an in-depth analysis of the text and relevant literature, the article demonstrates how Maṭlab al-Ṭālibīn highlights the crucial role of Kashmiri scholars in advancing tafsīr, while also enriching the intellectual discourse of 16th-century Islam. Although incomplete, covering only a small portion of the Qur’an, the work’s contribution is invaluable for understanding tafsīr in the Indian subcontinent, which at the time was influenced by major tafsīr works such as Tafsīr al-Qurtubī and al-Bayḍhāwī. The study also addresses the challenges faced in preserving the manuscript of Maṭlab al-Ṭālibīn, which currently exists in a very fragile condition. The article emphasizes the importance of transcription and conservation efforts to ensure that this work can continue to be studied and analyzed by future generations. Thus, this research not only contributes to the understanding of tafsīr in Kashmir but also broadens the scope of tafsīr studies within the larger Islamic intellectual tradition.